Bone mesenchymal stem cells-derived miR-223-3p-containing exosomes ameliorate lipopolysaccharide-induced acute uterine injury via interacting with endothelial progenitor cells. Issue 2 (20th December 2021) - Liu, Yana; Zhang, Shihong; Xue, Zhiwei; Zhou, Xiaoxia; Tong, Lin; Liao, Jiachen; Pan, Huan; Zhou, Shu
ABSTRACT: Bone mesenchymal stem cells (BMSCs) have been used for the treatment of acute uterine injury (AUI)-induced intrauterine adhesion (IUA) via interacting with the endothelial progenitor cells (EPCs), and BMSCs-derived exosomes (BMSCs-exo) may be the key regulators for this process. However, the underlying mechanisms have not been studied. Based on the existed literatures, lipopolysaccharide (LPS) was used to induce AUI in mice models and EPCs to mimic the realistic pathogenesis of IUA in vivo and in vitro . Our data suggested that LPS induced apoptotic and pyroptotic cell death in mice uterine horn tissues and EPCs, and the clinical data supported that increased levels of pro-inflammatory cytokines IL-18 and IL-1β were also observed in IUA patients' serum samples, and silencing of NLRP3 rescued cell viability in LPS-treated EPCs. Next, the LPS-treated EPCs were respectively co-cultured with BMSCs in the Transwell system and BMSCs-exo, and the results hinted that both BMSCs and BMSCs-exo reversed the promoting effects of LPS treatment-induced cell death in EPCs. Then, we screened out miR-223-3p, as the upstream regulator for NLRP3, was enriched in BMSCs-exo, and BMSCs-exo inactivated NLRP3-mediated cell pyroptosis in EPCs via delivering miR-223-3p. Interestingly, upregulation of miR-223-3p attenuated LPS-induced cell death in EPCs. Collectively, we concluded that BMSCs-exo upregulated miR-223-3p to degrade NLRP3 in EPCs, which further reversed the cytotoxic effects of LPS treatment on EPCs to ameliorate LPS-induced AUI.